Scribal practice, text and canon in the Dead Sea scrolls : essays in memory of Peter W. Flint - Collins, John J. 1938-; Geyser-Fouché, Ananda, (Studies on the Texts of the Desert of Judah;, 2019)
This volume contains 17 essays on the subjects of text, canon, and scribal practice. The volume is introduced by an overview of the Qumran evidence for text and canon of the Bible. Most of the text critical studies deal with texts from the Dead Sea Scrolls, including sectarian as well as canonical texts. Two essays shed light on the formation of authoritative literature. Scribal practice is illustrated in various ways, again mostly from the Dead Sea Scrolls. One essay deals with diachronic change in Qumran Hebrew. Rounding out the volume are two thematic studies, a wide-ranging study of the "ambiguous oracle" of Josephus, which he identifies as Balaam's oracle, and a review of the use of female metaphors for Wisdom.